A unique presentation of four thrombotic events at a time. (27th November 2012) - Rajani, Ali Raza; Hussain, Kosar; Baslaib, Fahad Omar; Radaideh, Ghazi Ahmad
Abstract : A 72-year-old man was referred to our hospital as a case of postcardiac arrest following a long distance air flight. Work-up in the emergency department revealed the presence of deep vein thrombosis (DVT), bilateral pulmonary embolism, inferior STEMI (ST elevation myocardial infarction) and ischaemic stroke. He received thrombolysis by recombinant tissue plasminogen activator (tPA) following which his haemodynamic status improved, but he developed haemorrhagic transformation of the stroke as a complication. The haemorrhagic lesion gradually resolved with conservative management, leaving behind a residual neurological deficit. His haemodynamic status was stable after the management. Although a diagnosis of right-to-left shunt lesion was highly suggestive in this condition, it could not be confirmed on the transthoracic echocardiogram.  Our patient had a unique presentation of multiple thrombi in different organs that caused significant morbidity and haemodynamic instability. There are no well-established guidelines that discuss the acute management of such cases. This situation requires a careful assessment and management of the patient by a multidisciplinary team.